Effect of Permeability Heterogeneity on Area of Review. (July 2017) - Pawar, Rajesh; Dempsey, David; Guthrie, George
Abstract: The Area of Review is one of the most important aspects of a geologic CO2 storage site permit application and regulatory requirement. The US Environmental Protection Agency (EPA) has implemented an Area of Review (AoR) requirement for Class VI CO2 injection wells for geologic sequestration. Reservoir permeability is one of the most important parameters controlling AoR evolution but is generally highly heterogeneous and difficult to constrain. We have used a numerical model for Rock Springs Uplift in Wyoming as an example site to characterize how the heterogeneity in reservoir permeability affects AoR. We have performed multiple reservoir simulations using multiple, equally-likely realizations of heterogeneous permeability. We considered multiple CO2 injection scenarios with varying injection rates as well as varying injection and post-site durations. Results of our study demonstrate that uncertainty in permeability heterogeneity can significantly influence AoR for both CO2 saturation and pressure. In our example, the CO2 AoR varied by as much as 2-3 times while the pressure AoR varied over 1.5 – 2 times. Such type of variability can have significant implications in defining AoR for site permit applications.